2016
DOI: 10.1037/xhp0000129
|View full text |Cite
|
Sign up to set email alerts
|

Reward favors the prepared: Incentive and task-informative cues interact to enhance attentional control.

Abstract: The dual mechanisms of control account suggests that cognitive control may be implemented through relatively proactive mechanisms in anticipation of stimulus onset, or through reactive mechanisms, triggered in response to changing stimulus demands. Reward incentives and task-informative cues (signaling the presence/absence of upcoming cognitive demand) have both been found to influence cognitive control in a proactive or preparatory fashion; yet, it is currently unclear whether and how such cue effects interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
77
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 73 publications
(85 citation statements)
references
References 49 publications
(93 reference statements)
5
77
3
Order By: Relevance
“…On this timescale, DA neurons have been shown to exhibit gradually increasing (ramping) anticipatory activity, scaling with reward uncertainty (Fiorillo et al, 2003). Given prior argument that uncertainty serves to signal cognitive control demand (Mushtaq et al, 2011), we suggest that a similar ramping signal could have supported enhanced control, in response to task-informative cues, in Chiew and Braver (2016). Potential commonalities in cognitive control and memory effects following brief reward anticipation (corresponding to phasic DA) are less straightforward, but observed control performance (response speeding without enhanced control) and memory performance (enhanced consolidation-dependent memory scaling with expected reward value) dovetail with prior evidence for DA involvement in response speeding and episodic encoding.…”
Section: Future Directionssupporting
confidence: 53%
See 4 more Smart Citations
“…On this timescale, DA neurons have been shown to exhibit gradually increasing (ramping) anticipatory activity, scaling with reward uncertainty (Fiorillo et al, 2003). Given prior argument that uncertainty serves to signal cognitive control demand (Mushtaq et al, 2011), we suggest that a similar ramping signal could have supported enhanced control, in response to task-informative cues, in Chiew and Braver (2016). Potential commonalities in cognitive control and memory effects following brief reward anticipation (corresponding to phasic DA) are less straightforward, but observed control performance (response speeding without enhanced control) and memory performance (enhanced consolidation-dependent memory scaling with expected reward value) dovetail with prior evidence for DA involvement in response speeding and episodic encoding.…”
Section: Future Directionssupporting
confidence: 53%
“…Prolonged reward anticipation was associated both with enhanced control (Chiew and Braver, 2016) and with enhanced memory for incidental stimuli (Stanek et al, submitted); however, in both studies, these effects were specifically seen in interaction with other experimental factors. Chiew and Braver demonstrated that while interference was lower under prolonged vs. brief reward anticipation (Early vs. Late Incentive), a specific control benefit was observed in Early Incentive informed trials.…”
Section: Reward Anticipation Dynamics: Synthesizing Across Findingsmentioning
confidence: 96%
See 3 more Smart Citations